Risk factors for obstetric anal sphincter injuries (OASIS) during vacuum extraction delivery in a university affiliated maternity hospital. (18th March 2020) - Segal, David; Baumfeld, Yael; Yahav, Lior; Yohay, David; Geva, Yael; Press, Fernanda; Weintraub, Adi Y.
Abstract: Introduction: Instrumental delivery is a well-known risk factor for obstetric anal sphincter injuries (OASIS). The specific characteristics among patient undergoing vacuum extraction delivery (VE) are less studied. Therefore, we aimed to evaluate risk factors for OASIS among parturient that underwent a VE delivery in a large university affiliated maternity hospital. Material and methods: The study population contained 9116 women who delivered by VE in tertiary medical center from 1988 to 2015. Inclusion criteria included deliveries beyond 24-week gestation. Multiple gestations and pregnancies complicated with stillbirth were excluded from the analysis. Maternal obstetric variables were compared between parturient with and without OASIS. Independent risk factors for OASIS were assessed by multivariable logistic regression modeling. Results: OASIS was diagnosed in 94 women (1.03%) following vacuum extraction. Among patients who underwent a VE delivery, gravidity and parity were found to be significantly lower in patients with OASIS. A multivariable logistic regression model with OASIS as the outcome variable revealed that among women who underwent VE, while episiotomy and delivery of a macrosomic neonate were not independently associated with OASIS, a strong association between nulliparity and OASIS was found (OR 3.34; 95% CI 1.93–5.78; p < .001). Conclusions: OASIS is uncommon in our population. Vacuum extraction in nulliparous parturient is a significant risk factor for OASIS. Our results should be taken into account when managing nulliparous deliveries.